(untitled) (Diametros, 2011)
In this article I raise a number of issues concerning John McDowell’s widely influential revisionist reading of Kant. These have to do with what I see as his failure – despite ambitious claims in that regard – to overcome the various problematic dualisms that dogged Kant’s thought throughout the three Critiques. Moreover, as I show, they have continued to mark the discourse of those who inherit Kant’s agenda in this or that updated, e.g., ‘linguistified’ form. More specifically, I argue that McDowell’s ‘new’ reading amounts to no more than a series of terminological shifts or substitutions, such that (for instance) the well-known problem with explaining how ‘sensuous intuitions’ can be somehow synthesised with ‘concepts of understanding’ is replaced – scarcely resolved – by an equally opaque and question-begging appeal to Kantian ‘receptivity’ and ‘spontaneity’. My essay goes on to discuss a number of kindred dichotomies, among them that of nature and ‘second nature’, all of which can basically be seen as resulting from the normative deficit entailed by McDowell’s particular kind of half-way naturalizing project. I conclude that this project shows insufficient regard to the history of post-Kantian continental thought, in particular the similar problems faced by ‘subjective’ and ‘objective’ idealists like Fichte and Schelling.